Anemia and associated factors among pregnant women attending antenatal care in public health facilities of Garowe City, Puntland, Somalia - Abdirisak Nur Yusuf; Adisu Birhanu; Alemayehu Tesfaye; Birhanu Shegene; Obsan Kassa; Tadesse Gure Eticha; Dawit Firdisa; Berhe Gebremichael (PLoS ONE, 2026)
Background Anemia is a prevalent global public health issue, especially among pregnant women in developing countries. Limited research exists on anemia in pregnant women in Somalia, particularly in Garowe City. This study aims to determine the prevalence of anemia and its associated factors among pregnant women attending antenatal care in public health facilities in Garowe City, Puntland, Somalia, from December 1, 2023, to January 1, 2024. Methods An institution-based cross-sectional study was conducted with 422 randomly selected pregnant women in public health facilities. Data were collected using EpiData version 4.6 and analyzed with SPSS version 25. Bivariate and multivariable logistic regression analyses identified factors associated with anemia, with statistical significance set at P < 0.05. Results The prevalence of anemia among pregnant women was 38.6% (95% CI: 33.9%, 43.6%). Significant associated factors included: rural residence (AOR = 2.58, 95% CI: 1.18–5.64), multigravidity (AOR = 2.01, 95% CI: 1.03–3.89), lack of nutritional counseling (AOR = 1.65, 95% CI: 1.09–2.52), positive malaria test (AOR = 3.58, 95% CI: 1.08–11.98), and not consuming one extra meal (AOR = 2.19, 95% CI: 1.15–4.19). Conclusions Anemia in pregnant women in Garowe City is a moderate public health concern according to WHO standards. Factors such as residence, gravidity, nutritional counseling, malaria status, and dietary habits significantly correlate with anemia. Public health measures should focus on enhancing nutritional counseling, promoting extra meal consumption, and preventing malaria during pregnancy.